Stomatopod-inspired integrate-and-fire triboelectric nanogenerator for harvesting mechanical energy with ultralow vibration speed. (15th April 2022) - Xu, Zhongwei; Li, Dianlun; Wang, Kun; Liu, Ye; Wang, Jiaxin; Qiu, Zhirong; Wu, Chaoxing; Lin, Jintang; Guo, Tailiang; Li, Fushan
Highlights: An integrate-and-fire triboelectric (IF-TENG) is developed to realize speed amplification. Input mechanical energy from ultralow-speed vibrations can be firstly integrated, and then be instantaneously released in full. Charged friction layers can move at a high speed, leading to a high output current. IF-TENG can stabilize the output current at different vibration speeds. IF component could be introduced to both vertical contact-separation and lateral-sliding mode. Abstract: Effective utilization of natural slight vibration with small movement speed is beneficial to development of energy harvest technology for solving energy problems. However, obtaining high current output when harvesting mechanical energy with ultralow vibration speed is difficult. Here, inspired by stomatopod (mantis) shrimp that has the ability to release pre-stored energy in a rapid action for generating an extremely fast strike, we propose an integrate-and-fire triboelectric (IF-TENG) to realize speed amplification. In this device, input mechanical energy from ultralow-speed vibrations can be firstly integrated, and then be instantaneously released in full when reaching a threshold. Thus, charged friction layers of the TENG can move at a high speed, leading to a relatively high output current. In addition to the speed amplification, the IF-TENG can stabilize the output current at different vibration speeds. Furthermore, we demonstrate that the idea of IF component could be introduced to both vertical contact-separation and lateral-sliding mode TENG for output performance enhancement, which supplies an efficient way for converting ultralow-speed vibration into electricity.